Evaluation of Celecoxib Addition to Pain Protocol After Total Hip and Knee Arthroplasty Stratified by Opioid Tolerance. Issue 10 (October 2015) - Kazerooni, Rashid; Tran, Michael H.
<x xml:space="preserve">Abstract</x> Objective: This study seeks to determine the impact that celecoxib has on patients' postoperative opioid consumption on the basis of whether the patient is opioid naive or opioid tolerant for total hip and knee arthroplasty. Methods: This was a retrospective study over 1.5 years that encompassed a preperiod and postperiod for adding celecoxib to the pain protocol. Prescriptions for opioids dispensed 6 months before surgery were analyzed to assess for preoperative opioid tolerance. Unadjusted results were presented. Primary outcome measure was change in milligrams of morphine per day associated with celecoxib use as per linear regression analysis. Secondary outcome measures included total opioid dose, average pain score, length of stay, and as-needed opioid doses. Results: Analysis included 142 patients. Unadjusted results showed that opioid-naive patients had greater reductions in opioid dose per day with celecoxib (49.1 vs. 80.8 mg) compared with tolerant patients (86.6 vs. 100.1 mg). Regression results showed similar results, with opioid-naive patients having a 29.9 mg reduction (95% confidence interval, −47.9 to −12.1; P=0.009) in opioid use per day associated with celecoxib use versus 5.5 mg reduction (95% confidence interval, −33.6 to 22.5; P=0.69) for opioid-tolerant group. Opioid-naive patients also had significant reductions in pain scores, as-needed opioid doses, and total opioid dose. Opioid-tolerant patients had significant reductions only in pain scores. Conclusions: Both opioid-tolerant and opioid-naive patients benefited from celecoxib therapy, although in different ways. Opioid-tolerant patients saw benefits other than reductions in opioid use; opioid-naive patients had similar benefits, but also had significant reductions in opioid use.